1944
DOI: 10.1084/jem.79.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugation and Ultrafiltration Studies on Allantoic Fluid Preparations of Influenza Virus

Abstract: The property of influenza virus suspensions to agglutinate red blood ceils appears to be closely associated with the infective activity of the virus (1). The complement-fixing antigen, on the other hand, has been shown to consist of two distinct fractions: one is intimately associated with the hemagglutinin and infective virus particle, while the other has a smaller size and is readily separable from the virus particle by centrifugation or adsorption with red blood ceils (2). A preliminary report (3) showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1944
1944
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…The sedimentation constants obtained are listed in Table I and can be compared with the values of 600 to 800 reported for PR8 virus particles (6,9,12). A single boundary, which was usually quite sharp, was observed with preparations containing 2 to 3 rag.…”
Section: Sedimentation Constantmentioning
confidence: 87%
See 1 more Smart Citation
“…The sedimentation constants obtained are listed in Table I and can be compared with the values of 600 to 800 reported for PR8 virus particles (6,9,12). A single boundary, which was usually quite sharp, was observed with preparations containing 2 to 3 rag.…”
Section: Sedimentation Constantmentioning
confidence: 87%
“…However, the presence of a 30 S component in centrifugally purified preparations of F12 influenza virus has been well established (10,18) and it has recently been shown that this component, contrary to earlier conclusions, is not the virus (10). In addition, a non-viral small component has been observed in purified preparations of Lee virus (29) and components having sedimentation constants ranging from 75 S to 450 S have been reported for preparations of PR8 virus (12,30). The small components in purified preparations of influenza virus are demonstrable by means of the ultracentrifuge mainly in concentrated solutions; i.e., 10 to 30 rag.…”
Section: Relation Of the Small Components Of Strains Of Influenza Virmentioning
confidence: 98%
“…virus has shown that the infective and hemagglutinating properties of the virus are removed with the 600-S component (14). The toxic factor described by Henle and Henle (9) has not been dissociated from the infective particle.…”
Section: Effect Of Saline Suspensions Of Virus--ultracentrifugal Anamentioning
confidence: 99%
“…If these calculations were restricted to the seed virus actually adsorbed onto the cells, the increase would be nearly 100-fold. Since agglutination by intact virus can be detected when the number of virus particles nearly equals that of the red cells (5,6,8,9,23,24) its efficiency per se cannot be improved. The seed virus would have to disintegrate, therefore, into 30 or 100 smaller units, respectively, if the NIHA obtained in the above experiments represented breakdown products.…”
Section: Discussionmentioning
confidence: 99%